The utilization of medical plants as a traditional drug in women in community of Mentok Sub-district, West Bangka - Rachmawati Felani Djuria; Eva Dewi R Purba; M. Seto Sudirman (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Many types of plants can be explored as ingredients in traditional medicine. One of the uses of plants as traditional medicine is herbal concoctions for postpartum mothers. Traditional healers (Hatra) use herbal ingredients in the treatment of postpartum mothers who have prepared these herbs in ready-to-use medicinal dosage forms (solid dosage forms such as pills, powders, and parem). The use of herbs or herbs should pay attention to the aspects of monitoring the distribution and supervision of traditional medicines. This research activity is carried out to increase public knowledge in the form of training in making traditional medicines and providing information related to registration and distribution permits for traditional medicines. The type of research used is experimental design with the pretest-posttest only control group. The intervention method used is providing counseling, discussion, and training in making traditional medicines in the treatment of postpartum mothers. The study was conducted in the Mentok Subdistrict in Tanjung Village, West Bangka Regency from March - to October 2020. The study used 29 people with total sampling techniques (health cadres and mothers of Family Welfare Empowerment) and analyzed bivariate using the dependent t-test. The results of this service activity resulted in 4 traditional herbal remedies for delivery, namely parem stomach and body parem to clean dirt / dirty blood, brewed herbal medicine to remove stiffness/increase stamina, and brewed herbal medicine to avoid colds. The conclusion is that service activities are effective in increasing skills in making traditional herbal medicine for delivery and increasing the number of people who know how to make herbal medicine for delivery, which so far has only decreased in one family.